Germination of hibiscus sabdariffa L.following priming treatments - Norakliliriana, Binti Abdul Rahman (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study was conducted to evaluate the effectiveness of priming treatments in improving the germination of H. sabdariffa seeds. Three types of treatment used were hydropriming, osmopriming, and thermopriming. The seeds were scarified using sand paper to enhance imbibitions of water. Priming agents included distilled water, PEG 8000, and warm water at 400C, were used to prime the seeds for period of 0, 6, 12, 18, and 24 hours and evaluated for moisture content and germination. Results showed that highest moisture contents were from scarified H. sabdariffa seeds which were 74.31% in hydropriming, 72.21% in osmopriming (0.1 g/ml H2O PEG 8000), and 81.99% in thermopriming. Scarified seeds thermoprimed at 400C gave the highest germination percentage than other treatments that was 82% at 18 hours of priming. Generally, germination was increased and more uniform in all types of priming which indicated that seeds were exposed to favourable condition and achieved suitable physiological state for seed germination.